Performance Evaluation of Some Native Rice Cultivators of the Kaippad Farming System of Kerala State of India - KT Chandramohanan, VV Radhakrishnanm and KV Mohanan (Universal Journal of Agricultural Research, 2016)
Complex and ecologically responsive rice-fish farming systems have evolved in the coastal wetland regions of India over centuries. Kaippad is such an indigenous rice-fish farming system of coastal North Kerala in India. It is a natural system utilizing indigenous knowledge and local resources. The proximity to sea and subsequent periodic sea inundation ensure the uniqueness of this system. However kaippad farms are decreasing in area and the traditional salt tolerant rice cultivars cultivated in the area are also slowly receding from the scene owing to low productivity. Performance evaluation of five popular rice cultivars was attempted based on performance index and cumulative performance index to find out the most promising among the traditional varieties. The study revealed that the cultivar Kuthiru ranked first based on the cumulative performance index calculated on the basis of thirteen characters including six growth characters and seven yield characters. The cultivars Kuttusan and Orkazhama ranked second and third. Selection and further improvement programmes using these cultivars will give rise to promising rice varieties suited for the needs of this special rice ecosystem